Evaluation of Bite Force and Masticatory Performance: Complete Denture vs Mandibular Overdenture Users - Possebon,Anna Paula da Rosa (2020)
Abstract: This cross-sectional observational study with 24 patients evaluated differences in bite force (BF) and masticatory performance (MP) between conventional complete denture (CCD) and implant mandibular overdenture (IMO) users and the correlation between these variables. The BF test was performed bilaterally with an occlusal force device. During the MP test, patients were asked to chew Optocal particles for 40 cycles. The Shapiro Wilk test was employed to verify the normality of the data, the student t test to identify differences between groups, and Pearson’s correlation to investigate interrelationships between variables. A multiple linear regression was subsequently performed via the stepwise method. P values ≤0.05 were considered statistically significant. Unlike IMO users, CCD users presented a significant difference (25.6%) in BF between the dominant and non-dominant chewing side (p=0.04). IMO users presented significantly higher BF (p=0.01) without presenting a dominant side (p=0.38), and also performed significantly better for the following MP parameters: MPX50 values decreased by 27.25% in IMO users (p=0.01), MPB decreased by 48.38% (p=0.01), and ME 5.6 decreased by 53.25% (p=0.02), while ME2.8 increased by 151.57% (p=0.01). The BF and MPX50 in the IMO wearers group were negatively correlated (-0.57; p=0.05); this correlation coefficient was the only parameter included in the multivariate regression model. IMO users have higher BF and better masticatory performance than CCD users, especially in terms of chewed particles size reduction. MP is correlated with a higher BF in IMO users through better particle trituration.